Improving Student’s Speaking Skill Through Communicative Language Teaching Method At SMK Alam Karya Bekasi - Safitri, Enung; A.E, Yon; Solo, Lenny (CV. ITTC INDONESIA, 2024)
The objective of this research is to investigate how the Communicative Language Teaching (CLT) method can improve students' speaking skills at SMK ALAM KARYA SUKAWANGI BEKASI during the 2023-2024 academic year. This study was conducted using Classroom Action Research (CAR) over two cycles, involving 28 students from Class XI as research subjects. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The results indicated a significant improvement in speaking skills among the students. By the end of the second cycle, 27 out of 28 students (96%) exceeded the Minimum Competency Criteria (KKM), while only one student (4%) remained below this threshold. The application of the CLT method not only enhanced the students’ speaking abilities but also increased their overall engagement in the learning process.This research highlights the effectiveness of innovative teaching models, specifically the use of the action research method in improving English learning outcomes for students. The findings have important implications for educational policy development, particularly in enhancing the quality of students’ learning achievements. Overall, the study provides valuable insights for educators looking to adopt more effective teaching strategies in language education.